If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-3=(4-x+1)
We move all terms to the left:
5x-3-((4-x+1))=0
We add all the numbers together, and all the variables
5x-((-1x+5))-3=0
We calculate terms in parentheses: -((-1x+5)), so:We get rid of parentheses
(-1x+5)
We get rid of parentheses
-1x+5
Back to the equation:
-(-1x+5)
5x+1x-5-3=0
We add all the numbers together, and all the variables
6x-8=0
We move all terms containing x to the left, all other terms to the right
6x=8
x=8/6
x=1+1/3
| X+3y=115 | | 7y-8=6-+1 | | -5x-12=-3x+8 | | 10-3x=15-x | | 2x+1/9-x-4/6=1 | | (19x-18)(7x+1)(10x-9)=180 | | -x-(-3x+2)=6 | | 20(a+1)=20 | | 15k−14k=9 | | 5(3-2x)+8x=7 | | 7s+6=13 | | 2(v+5)=20 | | 6y-6=3y-3 | | x^2+11x+17=5x-11 | | 19s−12s=14 | | x-2(2x-1)=11 | | X^2-2x=483 | | 5x=10=-50-5x | | 2x+29=9x-7 | | 3x+3(x+2)=18 | | F(x)=3^x+10x-2x-4 | | x/15=20/90 | | 7+4k=-3 | | 209=x^2+8x | | 2(y-6)-4=-2(-9y+1)-8y | | 0=x^2+8x-209 | | 87/100=x/4 | | 3x+41=-5(x-5) | | 4(-3)+3x=3 | | -7x-7=x-39 | | (x-5)^2=98 | | 4-6x=x+53 |